Biotechnology and conservation of medicinal plants - Dubey2, Dr. K. Sharma1* and Mrs S. (Journal of Experimental Sciences, 2011)
Plants have been an important source of medicine for thousands of years. Medicinal plants are the most important source of life saving drugs. Even today, the WHO estimates that up to 80 per cent of people still rely mainly on traditional remedies such as herbs for their medicines. Medicinal plants are resources of new drugs.Ã‚Â  Approximately one quarter of prescribed drugs contain plant extracts or active ingredients obtained from plant substances. Many of the modern medicines are produced indirectly from medicinal plants, for example aspirin and digitalis. Plants are directly used as medicines by a majority of cultures around the world, for example Chinese medicine and Indian medicine. Plants are directly used as medicines by a majority of cultures for example Chinese medicine and Indian medicine. Studying medicinal plants helps to understand plant toxicity and protect human and animals from natural poisons. This paper reviews the role of biotechnology for conservation of medicinal plants.